Membrane-Anchored Peptide Inhibits Human Immunodeficiency Virus Entry - Hildinger, Markus (American Society for Microbiology, 2001)
Peptides derived from the heptad repeats of human immunodeficiency virus (HIV) gp41 envelope glycoprotein, such as T20, can efficiently inhibit HIV type 1 (HIV-1) entry. In this study, replication of HIV-1 was inhibited more than 100-fold in a T-helper cell line transduced with a retrovirus vector expressing membrane-anchored T20 on the cell surface. Inhibition was independent of coreceptor usage.